BIBB/BAuA-Employment Survey 2018 - Hall, Anja [Verfasser]; Rohrbach-Schmidt, Daniela [Verfasser] (Bundesinstitut für Berufsbildung, 2020)
"This data and methods report contains a documentation of the research data from the 2018 BIBB/BAuA Employment Survey of the Working Population on Qualification and Working Conditions in Germany (in German: BIBB/BAuA-Erwerbstätigenbefragung 2018 - Arbeit und Beruf im Wandel, Erwerb und Verwertung beruflicher Qualifikationen). The survey was conducted by the Federal Institute for Vocational Education and Training (BIBB) in cooperation with the Federal Institute for Occupational Safety and Health (BAuA). The research data is available in standardised form for scientific purposes via the BIBB Research Data Centre (BIBB-FDZ)." (BIBB-Doku)
Keywords: T 3.4 Befragung; BIBB-/BAuA-Erhebung; Datengewinnung; Datendokumentation